Penerapan Strategi Love untuk Menemukan IKAGAI Guru Bimbingan dan Konseling Di Solok Selatan - Leni Murni Hayati; Firman Firman; Rizka Ahmad (Medan State University, 2021)
Abstract: The low attendance of BK teachers to school, the low level of attendance of BK teachers at MGBK, initially there were face-to-face hours to enter class because they were considered not to have a positive effect on BK services in schools. The purpose of this study is to innovate through the LOVE strategy to find Ikagai in BK teachers. The research method used is literature study and field observation. The results of the innovation of coaching BK teachers through MGBK at SMKN 1 Solok Selatan, BK teachers began to find ikagai in themselves as BK teachers, this can be seen from having started wanting to take part in seminar activities to increase competence as BK teachers in order to provide the best service to students foster.